Administrative barriers in the Russian economy as the conditions promoting corruption, and measures for their elimination - D. V. Manushin (Russian Journal of Economics and Law)
Objective: to reveal the main administrative barriers of the Russian economy, occurring in economic activity, to evaluate their interdependence with corruption and elaboration of counter measures. Method: abstract-logic. Results: It is proved that the methods of struggle against administrative barriers, existing in our country, do not significantly improve the condition of Russian organizations. The notion of “administrative barrier” is given. The sectors having the most of these barriers are listed. The current condition in the sphere of administrative barriers regulation is described, their interaction with corruption is shown. The author proposes measures in this field. Scientific novelty: the new detailed measures are proposed for overcoming the administrative barriers in the Russian economy. The mechanism of struggle against corruptive officials is elaborated. Practical value: The result should be to clear the Russian economy from majority of administrative barriers, to see new firms in the market, to activate competition and reduce the cost of their services.